High Frequency Analyzer (HFA) of Plasma Wave Experiment (PWE) onboard the Arase spacecraft - Atsushi Kumamoto (Earth, Planets and Space, 2018)
Abstract The High Frequency Analyzer (HFA) is a subsystem of the Plasma Wave Experiment onboard the Arase (ERG) spacecraft. The main purposes of the HFA include (1) determining the electron number density around the spacecraft from observations of upper hybrid resonance (UHR) waves, (2) measuring the electromagnetic field component of whistler-mode chorus in a frequency range above 20 kHz, and (3) observing radio and plasma waves excited in the storm-time magnetosphere. Two components of AC electric fields detected by Wire Probe Antenna and one component of AC magnetic fields detected by Magnetic Search Coils are fed to the HFA. By applying analog and digital signal processing in the HFA, the spectrograms of two electric fields (EE mode) or one electric field and one magnetic field (EB mode) in a frequency range from 10 kHz to 10 MHz are obtained at an interval of 8 s. For the observation of plasmapause, the HFA can also be operated in PP (plasmapause) mode, in which spectrograms of one electric field component below 1 MHz are obtained at an interval of 1 s. In the initial HFA operations from January to July, 2017, the following results are obtained: (1) UHR waves, auroral kilometric radiation (AKR), whistler-mode chorus, electrostatic electron cyclotron harmonic waves, and nonthermal terrestrial continuum radiation were observed by the HFA in geomagnetically quiet and disturbed conditions. (2) In the test operations of the polarization observations on June 10, 2017, the fundamental R-X and L-O mode AKR and the second-harmonic R-X mode AKR from different sources in the northern polar region were observed. (3) The semiautomatic UHR frequency identification by the computer and a human operator was applied to the HFA spectrograms. In the identification by the computer, we used an algorithm for narrowing down the candidates of UHR frequency by checking intensity and bandwidth. Then, the identified UHR frequency by the computer was checked and corrected if needed by the human operator. Electron number density derived from the determined UHR frequency will be useful for the investigation of the storm-time evolution of the plasmasphere and topside ionosphere.